MINOR CENTRES IN THE PONTINE PLAIN: THE CASES OF FORUM APPII AND AD MEDIAS. (2nd October 2014) - Tol, Gijs; de Haas, Tymon; Armstrong, Kayt; Attema, Peter
Abstract : Although both the urban and rural landscapes of Roman Italy have received due attention in current debates on the Roman economy, this is less true for the highly variable group of intermediate sites, here conveniently labelled as 'minor centres', and their role within economic networks. This contribution focuses attention on two such sites, Forum Appii and Ad Medias, situated in the Pontine plain (Lazio, central Italy) along the Via Appia. After addressing issues of definition and the current state of research, we shall approach the potential functions of such sites through geographic models. Next, we discuss the results of a programme of geophysical surveys and field walking on both case-study sites. The results obtained suggest that, although far from being a uniform settlement class, minor centres could perform crucial functions within local and regional economies. Based on the present data, Forum Appii developed into a centre of craft production and, with its river port, also became a trade hub of regional importance. Ad Medias functioned primarily as a small centre provisioning and servicing travellers and the local rural population. To conclude the article, we consider the implications of the results obtained in terms of future research strategies. Abstract : Mentre sia i paesaggi urbani sia quelli rurali dell'Italia romana hanno ricevuto una doverosa attenzione nel corrente dibattito sull'economia romana, lo stesso non si può dire per il gruppo di siti di tipo intermedio e il ruolo da loro giocato all'interno dei network economici. Essi sono enormemente variabili e in questo lavoro opportunamente etichettati come 'centri minori'. Il presente contributo focalizza l'attenzione su due siti di questo tipo: Forum Appii e Ad Medias nella Pianura Pontina (Lazio, Italia centrale), lungo la via Appia. Vengono trattate in prima istanza questioni relative alla definizione e allo stato attuale della ricerca, per poi affrontare tramite modelli geografici le potenziali funzioni di questo tipo di siti. Il contributo discute poi i risultati di un programma di indagini geofisiche e di ricognizioni topografiche nei due casi studio presi in considerazione. I risultati ottenuti suggeriscono come, sebbene lontani dal costituire una classe di insediamento omogenea, i centri minori potessero svolgere funzioni cruciali all'interno degli assetti economici locali e regionali. Stando ai dati oggi a disposizione, Forum Appii si sviluppò in un centro di manifattura artigianale e, con il suo porto fluviale, divenne anche un centro commerciale di importanza regionale. Ad Medias svolse in primo luogo il ruolo di un piccolo centro di approvvigionamento e di servizio per i viaggiatori e per la locale popolazione rurale. Per concludere, l'articolo prende in considerazione le implicazioni dei risultati ottenuti in relazione alle future strategie di ricerca.